THE VIEW ON THE DENTAL MORBIDITY INDICATORS OF THE CHILDREN UKRAINIAN NOGAI POPULATION AT THE XV CENTURY DEALS WITH THE NEW STUDYING METHODS USED FOR ANTHROPOLOGICAL MATERIAL FROM THE MAMAY GORA BURIAL GROUND - А.G. Toshchev; L.F. Kaskova; А.V. Аrtemev (Український стоматологічний альманах, 2020)
The subject matter was the children dental status having involved in study anthropological bone material different historical eras. The 133 remains skeletons of children were examined. The control and main groups consisted with the skeletons of children who had lived in the Nogai and Golden Horde periods, respectively, which in turn the last included children skeletons of earlier historical times.